2022
DOI: 10.3389/fviro.2022.906271
|View full text |Cite
|
Sign up to set email alerts
|

Mother-to-Child Transmission of HIV Within 24 Months After Delivery in Women Initiating Lifelong Antiretroviral Therapy Pre/Post-Conception or Postnatally; Effects of Adolescent Girl and Young Woman Status and Plasma Viremia Late in Pregnancy

Abstract: IntroductionMother-to-child-transmission (MTCT) of human immunodeficiency virus (HIV) can occur in pregnancy/in utero (IU), during childbirth/intrapartum (IP), or postpartum (PP) through breastfeeding from an infected mother to her infant. Burden of PP-MTCT and associated risk factors remain poorly described, especially in adolescent girls and young women (AGYW) aged 15–24 years. Furthermore, despite concerns on high postnatal seroconversions, there is paucity of data on the burden of subsequent MTCT rates.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…In this cohort, lack of plasma HIV-RNA suppression is common within the HIV-infected subgroup mainly due to new HIV diagnosis, hence not being on ART and/or suboptimal duration of ART-exposure [ 16 ]. HIV-MTCT rate is low as previously reported [ 17 ].…”
Section: Methodsmentioning
confidence: 51%
“…In this cohort, lack of plasma HIV-RNA suppression is common within the HIV-infected subgroup mainly due to new HIV diagnosis, hence not being on ART and/or suboptimal duration of ART-exposure [ 16 ]. HIV-MTCT rate is low as previously reported [ 17 ].…”
Section: Methodsmentioning
confidence: 51%
“…Viral load monitoring programs in the country among PMTCT clients may have a huge impact on viral load suppression, the local health system and program focus could affect the suppression rate [31]. Even though, the prevalence of low viral non-suppression was recorded, it had a critical impact on the program as well as for the offspring since HIV transmission is very high, the recent cohort study result also showed that the risk of HIV transmission was nine times more likely to transmit to the baby if the viral load result is non-suppressed in the time of pregnancy or breastfeeding [32].…”
Section: Discussionmentioning
confidence: 99%